Application of the Principle of Good Governance in the Activities of the European Court of Human Rights. - Dan Paranyuk, Serhiy Melenko (European Journal of Law and Public Administration, 2020)
Based on the methodology of performing axiological and logical-gnoseological analysis of juridically significant factors, the article under discussion presents a partial investigation of the practical application of one of the most fundamental principles of state functioning in the field of human rights protection. The object of investigation in the paper is the way the European Court of Human Rights (ECHR) perceives, understands and interprets the principle of Good Governance in the course of implementing it in Court’s activities. The precedents, formulated and adopted by the ECHR frequently acquire the status of legal sources for the member states of the Council of Europe. Therefore, the judiciary bodies of these countries have to rely in their practice on the conclusions, the ECHR came to in the course of considering certain cases. Qualitively equal understanding and application of the above decisions is a cornerstone in forming a common European legal space, as well as plays a leading role in the field of human rights protection, guaranteed by the European Convention for the Protection of Human Rights and Fundamental Freedoms of 1950 (hereinafter - the Convention) (Council of Europe, 1950). The principle of Good Governance is a complex notion. It directly or indirectly regards the rights and interests of both individuals (ensuring them certain rights and freedoms in a vast number of articles of the Convention) and social groups. This requires a complex analysis of the principle in both theoretical and practical aspects of its definition and application. Relying on the methodology of profound analysis of the axiological component of a certain legal phenomenon, like the content of some decisions of the Strasbourg Court, the authors of the article attempt to practically trace the implementation of the principle of Good Governance in the course of administering justice in Ukraine, as a member state of the Council of Europe. Therefore, the article under studies deals with the specifics of practical application of the principle of Good Governance in the ECHR activities, as well as with using precedent experience in the system of administrative judiciary of Ukraine.
Keywords: law, state, individual, justice, the principle of Good Governance, human rights, state’s obligations, the European Court of Human Rights, administrative judiciary, the effectiveness of regulatory-legal acts, state governing